2019
DOI: 10.1002/sctm.19-0202
|View full text |Cite
|
Sign up to set email alerts
|

Trends in mesenchymal stem cell clinical trials 2004-2018: Is efficacy optimal in a narrow dose range?

Abstract: The number of clinical trials using mesenchymal stem cells (MSCs) has increased since 2008, but this trend slowed in the past several years and dropped precipitously in 2018. Previous reports have analyzed MSC clinical trials by disease, phase, cell source, country of origin, and trial initiation date, all of which can be downloaded directly from ClinicalTrials.gov. We have extended analyses to a larger group of 914 MSC trials reported through 2018. To search for potential factors that may influence the design… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
286
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 311 publications
(306 citation statements)
references
References 59 publications
(78 reference statements)
10
286
0
1
Order By: Relevance
“…The number of stem cells currently used in clinical trials ranges from 10 7 to 10 9 cells [ 7 ]. Therefore, producing sufficient numbers of MSCs is very important in MSC therapy [ 8 , 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…The number of stem cells currently used in clinical trials ranges from 10 7 to 10 9 cells [ 7 ]. Therefore, producing sufficient numbers of MSCs is very important in MSC therapy [ 8 , 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…Although numerous in vitro and in vivo experiments in animal models have confirmed the therapeutic potential of MSCs [55], the clinical results have not been encouraging. To date, there are more than 500 ongoing MSC-based clinical trials, and more than ten products have been approved for listing globally [56], indicating that their safety and effectiveness are being recognized. Studies have shown that no serious adverse reactions have been observed in animal and human clinical trials of MSCs (bone marrow, fat, umbilical cord, or placenta) from either autologous or allogeneic sources.…”
Section: Resultsmentioning
confidence: 99%
“…However, many of them have not yielded the desired results (Trounson and McDonald, 2015) and their number has dropped over the years. This decline may be due to the fact that these preclinical and clinical trials are too heterogeneous: MSCs from different sources, different cell preparation protocols, and different cell passage numbers have been used over time (Kabat et al, 2020). Under these circumstances, the application of stem cell therapy to the surgical implantation of meshes for hernia treatment remains challenging.…”
Section: Discussionmentioning
confidence: 99%